2003
DOI: 10.1007/s10350-004-6619-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Surgery in Patients Belonging to Amsterdam-Positive Families

Abstract: We conclude that there is high risk of metachronous colorectal cancer if an index cancer in a hereditary nonpolyposis colorectal cancer patient (defined according to Amsterdam criteria) is treated by partial colectomy. However, this risk can be lowered by performing a total colectomy at the time of index surgery, or possibly by effective postoperative surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 15 publications
1
18
0
2
Order By: Relevance
“…Several studies reported that the risk of developing metachronous CRC varies between 22% and 41%. [7][8][9] We found a 10-year cumulative risk of developing CRC after partial colectomy of 16% in comparison with 3% after subtotal colectomy. 10 Moreover, with the use of a mathematical (Markov) model, we observed that subtotal colectomy was associated with a slightly increased life expectancy.…”
mentioning
confidence: 84%
“…Several studies reported that the risk of developing metachronous CRC varies between 22% and 41%. [7][8][9] We found a 10-year cumulative risk of developing CRC after partial colectomy of 16% in comparison with 3% after subtotal colectomy. 10 Moreover, with the use of a mathematical (Markov) model, we observed that subtotal colectomy was associated with a slightly increased life expectancy.…”
mentioning
confidence: 84%
“…The tumor type, location, stage and progression, as well as the patient's general health status should be considered. The treatment of choice involves curative surgical resection of each cancer, followed by radiotherapy and chemotherapy (16)(17)(18). The prognosis should be determined independently as a function of the tumor stage and treatment results for each cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is potentially a high risk of metachronous colorectal cancer if an initial cancer in a LS patient (defined according to Amsterdam criteria) is treated by partial colectomy. However, this risk can be lowered, either by performing a total colectomy at the time of initial surgery or possibly by effective postoperative surveillance (24). Both of our cases had 3 first degree relatives suffering from colon cancer and 2 successive generations were found to be effected.…”
Section: Discussionmentioning
confidence: 99%